1433Community Health Workers for non-communicable diseases: a systematic review and meta-analysis. (2nd September 2021) - Thapa, Rajshree; Thrift, Amanda; Mishra, Shiva Raj; Zaman, Sojib Bin; Zengin, Ayse
Abstract: Background: We evaluated the effectiveness of various community health workers (CHWs)-led interventions for several non-communicable diseases (NCD) risk-factors in both low- to middle-income countries (LMICs) and high-income countries (HICs). Methods: We included interventions by CHWs targeting the uptake of services for NCDs and conducted meta-analyses of randomized controlled trials. Net differences in blood pressure (BP), glycated hemoglobin (HbA1c ), fasting blood glucose, triglycerides, low-density lipoprotein-cholesterol (LDL-C) cholesterol, and body mass index (BMI) were calculated between intervention and control groups . Results: Seventy-three studies were included. CHWs-led interventions were effective in reducing systolic BP -2.94 mmHg [95% CI: -4.28 to -1.59; I 2 =73%], diastolic BP -1.59 mmHg [-2.54 to -0.64; 81% ], HbA1c % -0.31 [-0.45 to -0.17; 52%], and triglycerides -8.32 mg/dl [-13.54 to -3.10; 0.0%]. The mean change in HbA1c % was detectable in studies undertaken in HICs [-0.35 (-0.45 to -0.1)] but not in LMICs [-0.03 (-0.21 to 0.15)]. Interventions targeting diabetes were also effective in reducing systolic BP by -2.30 mmHg (-4.22 to -0.38). There was no evidence that these interventions reduced BMI or LDL-C. Conclusions: Engagement of CHWs is an effective strategy to reduce BP. They are also effective in reducing HbA1c and triglycerides in HICs; but further research is needed in LMICs. It also appears that interventions led by CHWs may be effective in reducing more than one risk factor simultaneously. Key messages: Engaging CHWs is an important strategy to combat the growing burden of hypertension.